Research on a Machine – Tractor Unit for Strip-Till Technology - Nadykto, Volodymyr; Domeika, R.; Golub, G.; Kukharets, S.; Chorna, T.; Čėsna, J.; Hutsol, T.; Надикто, Володимир Трохимович (Basel, Switzerland : Licensee MDPI, 2023)
EN: One of the most modern technologies for growing row crops is strip-till. Currently, it occupies an intermediate position between conventional tillage and no-till technologies. Special complex and expensive machines are used to implement strip-till technology practically. To avoid this, a combined unit is proposed, including a tractor and two simple machines: a front-disc harrow and a chisel plough mounted behind the tractor. As experimental studies have shown, this unit makes implementing the strip-till one-pass technology possible. In this case, the oscillations process in the soil-loosening depth of strips is low-frequency since at least 95% of this statistical parameter variance is concentrated in the frequency range of 0–16.8 s 1 or 0–2.7 Hz, and its maximum falls at a frequency of 0.4 Hz. The soil-loosening depth in the strips can deviate from the mean value by +-2 cmonce per 7.1 m of the combined unit’s path. With a mean speed of its movement of 2.1 ms 1, the release frequency of the mean value of the soil-loosening depth exceeding 2 cm is only 0.29 s or 0.05 Hz. Not less than 95% of the loosened strips’ non-straightness oscillations variance is in the frequency range of 0–0.25 m 1, and the value of the variance itself is small and amounts to 1.08 cm2. Proceeding from this, the non-straightness of the loosened strips by the combined unit can be considered satisfactory since its indicators meet the requirements for the non-straightness of row crops in terms of variance and frequency oscillations.
Keywords: chisel plough; non-straightness; tillage depth; unit’s adjacent pass; correlation function; variance’s spectrum